My Training Incumbent Is Doing a Good Job: An Empirical Investigation of Personal, Religious and Psychological Factors Shaping Curates' Evaluation of their Training Incumbent within the Anglican Church in England and Wales - Smith, Greg (Journal of Anglican studies, 2023)
Drawing on detailed questionnaire data (including personal, religious and psychological factors) provided by 416 pairs of curates and training incumbents, the present study addresses two core research questions. The first research question develops and tests a new measure: the Smith Attitude toward Training Incumbents Scale (SATIS). The second research question explores the influence of personal, religious and psychological characteristics of both the curate and the training incumbent in predicting curates' positive attitude toward the training incumbent. The data demonstrated that religious factors (Catholic or Evangelical, Liberal or Conservative, Charismatic or not Charismatic) were not significant. However, both personal and psychological factors of the curates themselves were significant. The curates who rated their training incumbent more highly were older and more emotionally stable. Personal factors were also significant for the training incumbents, but not psychological factors. The curates rated more highly the experience of working with younger training incumbents. The most satisfactory experience of curacy was associated with older and emotionally stable curates working with younger training incumbents.